Innovation relaxation belts to reduce labor pain itensity and increase β-endoprhine levels - Fitria, Candra Tyas Nur; Runjati, Runjati; Patriajati, Sutopo; Anwar, Choiroel (Universitas Muhammadiyah Purwokerto, 2020)
Background: Labor pain feels tremendous, and only 2-4% of mothers low pain during labor. Heat therapy is a non-pharmacological method. The heat therapy is still conventional, and this study uses a relaxation belt with more stable, dry heat media, and comfortable.Objective: This study aims to develop and test a relaxation belt for efforts to reduce labor pain intensity and increase β-endorphin levels in the primigravida of the active labor phase.Method: This study Research and Development (R&D). It consisted of 5 stages; stage I (literature study), stage II (product development), stage III (expert validity and phase I trials), stage IV (product revision and final product), and stage V (phase II trials).Results: The relaxation belt has been created, it has been validity experts test and field trials. The result that the relaxation belt is more effective in reducing pain and increasing β-endorphin levels than warm water compress (mean different pain labor 2.40; p<0.01; effect size 1.72 and mean different increasing β-endorphin levels 53,34; p<0.01; effect size 2.42).Conclusion: The relaxation belt is effective in reducing labor pain intensity and increasing β-endorphin levels.